2020
DOI: 10.1016/j.nbd.2020.104934
|View full text |Cite
|
Sign up to set email alerts
|

A Western diet impairs CNS energy homeostasis and recovery after spinal cord injury: Link to astrocyte metabolism

Abstract: A diet high in fat and sucrose (HFHS), the so-called Western diet promotes metabolic syndrome, a significant comorbidity for individuals with spinal cord injury (SCI). Here we demonstrate that the spinal cord of mice consuming HFHS expresses reduced insulin-like growth factor 1 (IGF-1) and its receptor and shows impaired tricarboxylic acid cycle function, reductions in PLP and increases in astrogliosis, all prior to SCI. After SCI, Western diet impaired sensorimotor and bladder recovery, increased microgliosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 130 publications
(83 reference statements)
3
20
0
Order By: Relevance
“…In addition, HFD-fed CD38ci mice showed significantly reduced IBA1 immunoreactivity in the ventral grey and white matter of the spinal cord compared to wildtype mice fed a HFD. Although HFD did not significantly increase IBA1immunoreactivity in this study, this is consistent with a recent Western-style diet study from our laboratory and older mice may already have residually higher levels (8,31).…”
Section: Diminished Neuroinflammatory Responses and Oxidative Damage supporting
confidence: 92%
See 4 more Smart Citations
“…In addition, HFD-fed CD38ci mice showed significantly reduced IBA1 immunoreactivity in the ventral grey and white matter of the spinal cord compared to wildtype mice fed a HFD. Although HFD did not significantly increase IBA1immunoreactivity in this study, this is consistent with a recent Western-style diet study from our laboratory and older mice may already have residually higher levels (8,31).…”
Section: Diminished Neuroinflammatory Responses and Oxidative Damage supporting
confidence: 92%
“…First, we established increased CD38 expression following HFD consumption. Our previous studies indicate that high fat diets lead to a reduction in oligodendrocytes and their progenitors within the mouse CNS (4,6,8). Next, we demonstrated that CD38 catalytically inactive mice fed a HFD were protected from HFD-mediated loss of oligodendrocytes with concomitant increases in NAD + levels and reduced neuroinflammation and oxidative damage.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations